Pulmonary Artery Banding for Ventricular Rehabilitation in Infants With Dilated Cardiomyopathy: Early Results in a Single-Center Experience - Di Candia, Angela; Castaldi, Biagio; Bordin, Giulia; Cerutti, Alessia; Reffo, Elena; Biffanti, Roberta; Di Salvo, Giovanni; Vida, Vladimiro L.; Padalino, Massimo A. (Frontiers in Pediatrics, 2020)
Background: Pulmonary artery banding (PAB) is reported as an innovative strategy for children with end-stage heart failure (ESHF) to bridge to transplantation or recovery. We report our early experience with PAB to evaluate outcomes, indications, and limitations. Materials and Methods: This is a single-center prospective clinical study, including infants and children admitted for ESHF owing to dilated cardiomyopathy (DCM) with preserved right ventricular function after failure of maximal conventional therapy. All patients underwent perioperative anticongestive medical therapy with ACE inhibitor, beta blocker, and spironolactone. Post-operatively, all patients underwent echocardiographic follow-up to assess myocardial recovery. Results: We selected five patients (four males) who underwent PAB at a median age of 8.6 months (range 3.9–42.2 months), with preoperative ejection fraction (EF) <30%. Sternal closure was delayed in all. One patient did not improve after PAB and underwent Berlin Heart implantation after 33 days, followed by heart transplant after 13 months. Four patients were discharged home on full anticongestive therapy. However, 2 months after discharge, one patient experienced severe acute heart failure secondary to pneumonia, which required mechanical circulatory support, and the patient underwent a successful heart transplant after 21 days. The remaining three patients are doing well at home, 22.4, 16.9, and 15.4 months after PAB. They all underwent elective percutaneous de-banding, 18.5, 4.8, and 10.7 months after PAB. EF increased from 17.7 ± 8.5% to 63.3 ± 7.6% (p = 0.03), and they have all been delisted. Conclusion: Use of PAB may be an effective alternative to mechanical support in selected infants for bridging to transplant or recovery. Better results seem to occur in patients aged <12 months. Further experience and research are required to identify responders and non-responders to this approach.